THE SONATA FOR CLARINET AND PIANO BY FRANCIS POULENC FROM THE POINT OF VIEW OF THE GENRE EVOLUTION OF THE 20th CENTURY SONATA - ROJNOVEANU ANGELA (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică, 2015)
The article focuses on the analysis of the Sonata for clarinet and piano by Francis Poulenc that still presents great interest nowadays. This is a masterpiece of twenty century music – an original composition considered from the point of view of its stylistic structure in the context of the experiments carried out in the composition techniques of last century. The author approaches problems of opus themes and architectonics as well as some aspects of musical language.